2013
DOI: 10.1371/journal.pone.0065290
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health and Cardiovascular Disease Incidence: Results from a Longitudinal Population-Based Cohort in Norfolk, UK

Abstract: IntroductionSelf-rated health (SRH) predicts chronic disease morbidity including cardiovascular disease (CVD). In a population-based cohort, we examined the association between SRH and incident CVD and whether this association was independent of socio-demographic, clinical and behavioural participant characteristics.MethodsPopulation-based prospective cohort study (European Prospective Investigation of Cancer-Norfolk). 20,941 men and women aged 39–74 years without prevalent CVD attended a baseline health exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 38 publications
(48 reference statements)
2
62
3
Order By: Relevance
“…However, several studies have shown that self-rated suboptimum health is strongly and consistently associated with allcause mortality (43,44) and with mortality and morbidity due to a range of chronic diseases including diabetes, heart disease, stroke and cancer (45)(46)(47). It is also strongly predictive for entering and losing paid employment (48,49) and, hence, a suitable measure of health to study in trajectories over time in the workforce.…”
Section: Schuring Et Almentioning
confidence: 99%
“…However, several studies have shown that self-rated suboptimum health is strongly and consistently associated with allcause mortality (43,44) and with mortality and morbidity due to a range of chronic diseases including diabetes, heart disease, stroke and cancer (45)(46)(47). It is also strongly predictive for entering and losing paid employment (48,49) and, hence, a suitable measure of health to study in trajectories over time in the workforce.…”
Section: Schuring Et Almentioning
confidence: 99%
“…The association between SRH and the incidence of cardiovascular disease has been discussed in previous studies 23. Benyamini et al showed that somatic sensations are possible manifestations of disease and powerful reminders of prior health risks, as well as potential indications of current and future health risks 24.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the infrequency of studies on this topic, we found that these findings corroborate those of other studies carried out in China, Athens, the United States and Sweden, which revealed a strong association between CVD and negative self-rated health (regular and poor) in adults (15,23) . A prospective study found that negative self-rated health is an indicative factor of the occurrence of CVD (24) . Thus, it is noteworthy that self-rated health is directly influenced by lifestyle behaviors, which in turn influence the health condition of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Along with being a measure centered on the patient, it is easy to obtain and provide real data representing a useful individual and population health indicator for those working in primary care and public health (24,28) . The results of this study show the importance of the health team recognizing the significance of the health problem for the individual who experiences it.…”
Section: Discussionmentioning
confidence: 99%